Photodynamic Inactivation of Candida Albicans Sensitized by Malachite Green - Mahdi, Rasoul A.; Mohammed, Aunce A. (Iraqi Journal of Laser, 2010)
The aim of this study is to investigate the ability of malachite green (MG) combined with 650nm diode laser to kill Candida albicans and to spectrally study the MG photodegradation after photodynamic therapy (PDT) spectrally. Cultures of Candida albicans were exposed to 40mW, 650 nm diode laser in the absence of MG. In PDT group, the MG was added to the Candida suspension for 5 min then exposed to diode laser for (5, 10, 15, 20) min at power density of 0.59W/cm2. The absorption spectrum of the photosensitized fungal suspension was obtained. The data were submitted to T-test (p<0.05). A 650nm diode laser in the presence of MG reduced the number of CFU/ml in 98.4%. Laser with 650nm alone and MG alone did not reduce significantly the number of CFU/ml of Candida albicans. Absorption spectrum showed that MG is photodegraded after irradiation .In conclusions, diode laser with 650nm was effective tool to photoinactivate Candida albicans in the presence of MG and that the dye is photodegraded following irradiation.